Analytical investigation of the main cable bending stiffness effect on free flexural vibration of suspension bridges with a 3D cable system. (July 2022) - Sun, Yuan; Zhang, Ming; Wang, Xiaoming; Zhao, Jianling; Bai, Yunteng
Abstract: This paper proposed a dimensionless continuum model of suspension bridges to comprehensively study the bending stiffness effect of the 3D cable system on the structural free flexural vibration, which has seldom been investigated in previous studies. In this model, coupled differential equations including the cable bending resistance term are derived via the Galerkin method. The equations are then nondimensionalized from a set of key design parameters, including the lateral inclination of hangers. The precision of the model is validated with the finite element (FE) method through an example. Then, parametric comparative studies of the effect under dimensionless parameters are conducted between 3D and 2D cable system suspension bridges. The results show that, the bending stiffness effects of the 3D cable system are more evident on the high order modes and antisymmetric modes of suspension bridges, which is similar with those effects of the 2D cable system. The hanger lateral inclination restrains the effect on the structural frequencies following a relationship of linear negative correlation; when the inclination angle varies from 30 to 60 degrees, the effect ratio of 3D to 2D cable system correspondingly varies from 0.33 to 0.67. Under a given hanger lateral inclination (48.6 degrees) with other identical conditions, the variation trend of the effects on the high order frequencies are similar between 3D and 2D cable systems; the effect value of the 3D cable system is on average 0.625 times that value of the 2D cable system.